Motivasi Masyarakat Terhadap Pengalihan Fungsi Lahan Hutan Menjadi Lahan Pertanian Di Desa Bakubakulu Kecematan Palolo Kabupaten Sigi - Rizaldy, Dedy Wahyu; Rachman, Imran; Dg. Massiri, Sudirman (Jurnal Warta Rimba, 2019)
Change of function of forest land is a change in the function of the main forest into non-forest areas such as, settlements, agricultural areas and plantations. The community has the incentive to perform the function of forest land. The purpose of this study is to determine the community's motivation to transfer the function of forest land to agricultural land in the village. Bakubakulu Palolo Subdistrict, Sigi Regency. This research was carried out for three months, from May to June 2017. The research location was in Bakubakulu Village Palolo Subdistrict, Sigi Regency, Central Sulawesi. Data collection techniques in this study were carried out by using information retrieval through surveys (observation directly) to the object to be examined, including observations of actual conditions in the field consisting of observations of the conversion of the function of forest land into agricultural land by the community in Bakubakulu Village, Palolo District, Sigi Regency. The method used is descriptive in 1-3-5. The results of the study indicate the level of community motivation based on material needs is very high. The community conducts the conversion of the function of forest land into agricultural land in order to have productive land for agricultural / gardening activities in order to get good harvests. to meet daily needs.Keywords: Motivation, Forest Land Function Expert, Community